2008
DOI: 10.1080/01612840801981108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-Based Support for Women Living with Serious Mental Illness

Abstract: Relationships are critical to a woman's growth and development, yet when living with serious mental illness, developing and nurturing connections can be challenging. This qualitative study explored the nature and quality of support provided within relationships for 14 women with schizophrenia. Families were key supporters. Female friends with mental illness often provided a meaningful source of connection for participants. Problematic relationships, losses over time, and living in poverty were among the barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…Lack of authenticity referred to several concepts, including a loss of reciprocity, trust and honesty within relationships. Participants in a study by Chernomas et al (2008) also reported the importance of reciprocity in friendships. In line with recommendations of Chernomas and colleagues, further study into this concept is warranted.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Lack of authenticity referred to several concepts, including a loss of reciprocity, trust and honesty within relationships. Participants in a study by Chernomas et al (2008) also reported the importance of reciprocity in friendships. In line with recommendations of Chernomas and colleagues, further study into this concept is warranted.…”
Section: Discussionmentioning
confidence: 86%
“…1). Despite attempts and strategies to gain new friendships, several participants talked about the dearth of opportunities for meeting new people, a situation described elsewhere (Chernomas et al, 2008). The hope of forming new relationships was further complicated by a perceived inability to disclose one's mental illness, as described under the previous quadrant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Chernomas et al (2008) found that families were key support providers for women with schizophrenia. Female friends with mental illness often provided a meaningful source of connection.…”
Section: Theoretical Concepts and Previous Researchmentioning
confidence: 98%